2009
DOI: 10.1111/j.1440-1754.2009.01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sterile cerebrospinal fluid pleocytosis in infants with urinary tract infection

Abstract: Our results are compatible with published reports on the proportion of infants with UTI who have concurrent sterile CSF pleocytosis. We were able to exclude previous antibiotic therapy by measuring urinary anti-microbial activity. Our work supports the hypothesis that CSF pleocytosis in UTI is inflammatory and not because of infection of the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…In the remaining 14 studies included in this review, the rate of co-existing bacterial meningitis in infants with UTI ranged from 0% (six studies)2 7 8 11 13 14 to 2.0% (one study) 10. Notably, the latter study was relatively small and included only a single patient with co-existing meningitis.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…In the remaining 14 studies included in this review, the rate of co-existing bacterial meningitis in infants with UTI ranged from 0% (six studies)2 7 8 11 13 14 to 2.0% (one study) 10. Notably, the latter study was relatively small and included only a single patient with co-existing meningitis.…”
Section: Commentarymentioning
confidence: 99%
“…It is noteworthy that aseptic meningitis, which was addressed in only some studies,1 2 4 6 8 9 11 12 15 was identified in 5–18% of patients. Importantly, in only one study did the investigators exclude patients who had received antibiotics prior to presentation by analysing urine samples for antimicrobial activity 2.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that co-existing bacterial meningitis was present in six (19.4%) of the 31 infants with UTI who had a lumbar puncture. Subsequent studies have reported considerably lower estimates for the risk of co-existing meningitis in children presenting with UTI [3][7], [11][19]. However, the majority of studies have significant limitations, including small sample size [4], [6], [13], [15][19] and absence of a precise definition for UTI [12], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have reported considerably lower estimates for the risk of co-existing meningitis in children presenting with UTI [3][7], [11][19]. However, the majority of studies have significant limitations, including small sample size [4], [6], [13], [15][19] and absence of a precise definition for UTI [12], [17]. Furthermore, in the majority of previous studies, the study population exclusively comprised infants younger than three months of age, [3][6], [12], [14]–[18] and therefore only limited data exist regarding older infants, as well as children outside infancy.…”
Section: Introductionmentioning
confidence: 99%